Lower-extremity isokinetic strength ratios of elite springboard and platform diving athletes - Vieira, A.; Alex, S.; Martorelli, A.; Brown, L. E.; Moreira, R.; Bottaro, M. (The Physician and Sportsmedicine, 2017)
Objectives: The purpose of the present study was to examine knee extensor and flexor muscle strength ratios of an elite group of diving athletes.